Lower Detection Limit Enhancement for Low Concentration Ammonia Measurement - Hadi, Manap; Mohd Rusllim, Mohamed; M. S., Najib (Elsevier Ltd, 2016)

(untitled)
This paper describes an optical sensor system for quantifying ammonia at low concentration. An open path optical technique is used to measure ammonia concentration within the Ultraviolet region. Experimental results describing the operation of the sensor with wavelengths combination technique to enhance the Lower Detection Limit is presented. The results show the sensor is best measuring ammonia concentration at combination wavelengths (around 212 nm) with the Lower Detection Limit of 4.31 ppm and 1 s response time is achieved.